2015
DOI: 10.1016/j.jmoldx.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Broad-Panel PCR Assays for the Detection of Gastrointestinal Pathogens in Pediatric Oncology Patients

Abstract: Broadly multiplexed molecular amplification assays offer an unprecedented ability to diagnose gastrointestinal infection in immunocompromised patients. However, little data are available to compare the performance of such systems in this population. A total of 436 stool samples were collected from 199 predominantly immunocompromised pediatric oncology patients. Remnant samples were tested in parallel with the use of the premarket (investigational use only) versions of two broadly multiplexed PCR assays (BioFir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 20 publications
3
19
2
Order By: Relevance
“…Our data show that the two assays had similar detection rates with an overall concordance of greater than 90% for targets common to both assays, similar to other studies performed in different patient populations [9, 14]. The most frequent GI pathogens in our oncology patient population were C. difficile , Norovirus, Campylobacter, and Salmonella species.…”
Section: Discussionsupporting
confidence: 87%
“…Our data show that the two assays had similar detection rates with an overall concordance of greater than 90% for targets common to both assays, similar to other studies performed in different patient populations [9, 14]. The most frequent GI pathogens in our oncology patient population were C. difficile , Norovirus, Campylobacter, and Salmonella species.…”
Section: Discussionsupporting
confidence: 87%
“…was used for DNA samples. Norovirus I and II, sapovirus, adenovirus, and astrovirus real-time PCR primers, as well as, probes and conditions, were based on previous publications [4346]. …”
Section: Methodsmentioning
confidence: 99%
“…We showed that the singleplex rRT-PCR method ( 3 ) was unable to capture infections caused by noncanonical viruses and is, therefore, limited in its utility for accurate surveillance and diagnosis. Although our multiplex method was able to identify all canonical and 2 noncanonical viruses ( 4 ), it is possible that we missed infections with other strains. Given the limited knowledge about HAstV genotypes and clinical disease, particularly in immunocompromised persons, additional studies will be crucial to help develop better diagnostics to capture all known HAstV genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…We screened samples from 2008 by using a singleplex real-time reverse transcription PCR (rRT-PCR) ( 3 ), an in-house multiplex PCR to identify canonical (HAstV1–8) and noncanonical (MLB1 and VA2) genotypes ( 4 ), and endpoint PCRs by using primers targeting open reading frame (ORF) 1( 5 ) and ORF2 ( 6 , 7 ). The singeplex method detected HAstV in 23/72 samples, compared with 61/67 (5 samples were not tested) by the multiplex method.…”
Section: The Studymentioning
confidence: 99%